1996
DOI: 10.1159/000246375
|View full text |Cite
|
Sign up to set email alerts
|

Emollients and Photo(chemo)therapy: A Call for Caution

Abstract: Background: Emollients used for skin care, treatment of a disease or lubrication, before irradiation during the course of phototherapy or photochemotherapy, may significantly interfere with the transmission of UV light and may influence the outcome of the therapy. Objective: These experiments should characterize and quantify the possible interactions of usual emollients with UV light transmission. Method: The method was an in vitro technique similar to the one already used for the determination of sun protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 8 publications
1
22
0
1
Order By: Relevance
“…Similarly, Berne et al (13) reported that oil‐in‐water emollients can enhance the effectiveness of UV‐B phototherapy. Gabard et al (15) also concluded that emollients can significantly modify the outcome of phototherapy. However, no controlled clinical studies have been published to substantiate this claim in childhood psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Berne et al (13) reported that oil‐in‐water emollients can enhance the effectiveness of UV‐B phototherapy. Gabard et al (15) also concluded that emollients can significantly modify the outcome of phototherapy. However, no controlled clinical studies have been published to substantiate this claim in childhood psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,18,19 Two studies 3,5 showed that UV transmission may be enhanced by emollients while two reported the contrary, 1,18 with Otman et al 1 concluding that, in the NB-UVB range, 23 of 30 emollients had a monochromatic protection factor (MPF) of 1AE2 or above -a result considered clinically significant in order to avoid a decrease of UV transmission. 1,3,5,18,19 Two studies 3,5 showed that UV transmission may be enhanced by emollients while two reported the contrary, 1,18 with Otman et al 1 concluding that, in the NB-UVB range, 23 of 30 emollients had a monochromatic protection factor (MPF) of 1AE2 or above -a result considered clinically significant in order to avoid a decrease of UV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure changes the consistency of the substance and creates additional problems with respect to comparability. In most determinations of the UV protection of lubricant emollients performed in vitro , 22,23 the calculated UV protection factor is too high, 24 i.e. the estimated transmission is too low; this is the consequence of paying too little attention to the optical properties of the skin.…”
Section: Discussionmentioning
confidence: 99%